The world's highest-paid athletes, product endorsement, and Twitter. Issue 3 (10th July 2017) - Abeza, Gashaw; O'Reilly, Norm; Séguin, Benoit; Nzindukiyimana, Ornella
Abstract : Purpose: The purpose of this paper is to examine the practice of celebrity athletes' product endorsement in the context of social media, guided by meaning transfer model. Design/methodology/approach: The study adopted a content analysis method based on data gathered from the official Twitter account of 17 of the highest-paid athletes over a period of five months. Findings: Results outline the state, involvement level, roles, modes, preferred content types, discernible differences, shared features, and best practices employed in endorsement tweets. A framework of athletes' product endorsement on Twitter is presented. Research limitations/implications: The study presented theoretical and practical implications, and limitations and impetus for future research. Originality/value: The study investigated professional athletes' use of their own media channel for the purpose of endorsement, presented a framework that illustrates the practice of celebrity athletes' product endorsement on social media, and identified a best practice and an exemplary reference.